AUGMENTED REALITY (AR) AND VIRTUAL REALITY (VR): THE FUTURE OF INTERACTIVE VOCATIONAL EDUCATION AND TRAINING FOR PEOPLE WITH HANDICAP - Mekacher, Leila (PUPIL: International Journal of Teaching, Education and Learning, 2019)
The aim of this paper is to present our didactic-methodical concept for a virtual interactive vocational education and training using the VR and AR technologies. Since we are a dual VET Institutions for handicapped, we primarily focus on young people with special needs, autism, and significant social interaction difficulties. Our concept can also be applied to other target groups. The virtual environment offers the trainees the ability to interact and experiment with items and constructs in a similar way they would do in real world. The AR-Glasses promise through the free visualization meaningful application scenarios for the teaching and learning concept; the wearer is supported during his activity by additional context-based virtual information and objects. Our method is based on the educational goals, the cognitive and psychophysiological aspects of the trainees, the technological aspects and the pedagogical strategies of goal-oriented teaching. In this paper we present some application examples of these technologies in different areas of our VET such as automotive mechatronics engineering, electrotechnology and Automation, technical product design, information technology and In-house virtual vocational School.